1995
DOI: 10.1136/ard.54.10.801
|View full text |Cite
|
Sign up to set email alerts
|

Risk of vertebral fracture and relationship to bone mineral density in steroid treated rheumatoid arthritis.

Abstract: Objectives-To determine the prevalence of vertebral fracture in postmenopausal women with steroid treated rheumatoid arthritis (RA), and whether the risk of vertebral fracture could be predicted from measurements of bone mineral density (BMD).Methods-Vertebral deformities were defined from spine radiographs in 76 postmenopausal women with steroid treated RA (aged 50-79 years) and 347 age matched women from a population based group, using a morphometric technique. Lumbar spine (LS) BMD was measured by dual ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
151
3
19

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(180 citation statements)
references
References 24 publications
7
151
3
19
Order By: Relevance
“…Studies of patients using daily doses on average of 7.5 mg prednisolone or lower at the time of BMD measurement found conflicting results. Several studies found no substantive reductions in BMD at lower doses [15,16,18,26,28,37,39,[54][55][56][57]102,103], in contrast to others [29,30,36,43,47,68,98,105]. Interpretation of these results is complicated because the daily doses used prior to the BMD measurement were frequently unknown and not taken into account.…”
Section: Relationship To Cs Dosementioning
confidence: 55%
See 3 more Smart Citations
“…Studies of patients using daily doses on average of 7.5 mg prednisolone or lower at the time of BMD measurement found conflicting results. Several studies found no substantive reductions in BMD at lower doses [15,16,18,26,28,37,39,[54][55][56][57]102,103], in contrast to others [29,30,36,43,47,68,98,105]. Interpretation of these results is complicated because the daily doses used prior to the BMD measurement were frequently unknown and not taken into account.…”
Section: Relationship To Cs Dosementioning
confidence: 55%
“…Other studies have published conflicting results on individual susceptibility to fractures. Naganathan et al [52] observed a higher increase in vertebral deformities in older users compared to younger users, whereas Peel et al [57] observed the converse.…”
Section: Susceptibility To Skeletal Effectsmentioning
confidence: 74%
See 2 more Smart Citations
“…In rheumatoid arthritis patients, treated with GC, the risk of vertebral fracture has been reported as having increased 6-fold compared with controls, whereas the reduction of lumbar spine BMD was only 0.79 SD (50). A recent meta-analysis on glucocorticoid-induced osteoporosis revealed that fractures occur at a much higher rate than expected on the basis of BMD, and that BMD changes during GC therapy may predict, only to a moderate extent, the increase in fracture risk (49).…”
Section: Dxamentioning
confidence: 99%